Effect of an elastic substrate on buckling of free‐standing nanocolumns. Issue 4 (18th November 2013) - Wu, J.X.; Li, X.F.
<x xml:space="preserve">Abstract</x> This paper studies the buckling problem of nanowires (NWs) and carbon nanotubes (CNTs) freely standing on a substrate and subjected to distributed axial loads. NWs and CNTs are modeled as elastic nanocolumns and due to their high Young's modulus, the substrate is reasonably considered as an elastic foundation. The junction between the nanocolumn and substrate is described by a rotational spring. A new approach is suggested to solve the stability of axially‐loaded nanocolumns with a rotational spring junction. An approximation expression for the critical load with high accuracy is derived in closed form. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>